2008
DOI: 10.1016/j.jtcvs.2007.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Isolating the entire posterior left atrium improves surgical outcomes after the Cox maze procedure

Abstract: Isolating the entire posterior left atrium by creating a box lesion instead of a single connecting lesion between the pulmonary veins showed a significantly lower incidence of early atrial tachyarrhythmias, higher freedom from atrial fibrillation recurrence at 1 and 3 months, and lower use of antiarrhythmic drugs at 3 and 6 months. A complete box lesion should be included in all patients undergoing the Cox maze procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 35 publications
5
71
0
3
Order By: Relevance
“…1307 Further recent work has shown significantly improved results when the entire posterior LA is excluded by the so-called box lesion. 1306,1308 …”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“…1307 Further recent work has shown significantly improved results when the entire posterior LA is excluded by the so-called box lesion. 1306,1308 …”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“…Of note, part of these lines were made on an anatomic basis without verifying that conduction block had indeed been established. Whether additional lesions during either CA or SA would be beneficial for specific patient populations remains to be determined 24,25 ; this study was not designed or powered to answer that question.…”
Section: Procedural Effects Of Sa and Camentioning
confidence: 99%
“…12) Our results revealed that isolation of the entire posterior left atrium was essential for the elimination of chronic AF during a long-term follow-up. Voeller et al 15) also reported the importance of the isolation of all pulmonary veins in the new Cox maze VI procedure, in which a complete box isolation of the whole pulmonary veins was performed using a bipolar radiofrequency clamp. The new Cox maze IV procedure improved the elimination rate of AF and decreased the occurrence of postoperative atrial tachycardia significantly as compared with the old Cox maze IV procedure (non-box pulmonary vein isolation procedure).…”
Section: Discussionmentioning
confidence: 99%